The dynamics of bullying in Islamic Boarding Schools: an analysis of the causal factors and their impacts - Ramli, Supian; Handoko, Yudo; Noer Mawaddah Ainina (Indonesian Journal of Islamic Religious Education, 2024)
This research investigates the causes, impacts, and prevention strategies of bullying in Islamic boarding schools through a literature review approach. Factors such as strict hierarchical structures, a culture of violence, lack of effective supervision, and delayed interventions have been identified as the main causes of bullying. The impacts on students include psychological disorders such as depression, anxiety, and low self-esteem, as well as social issues like isolation and difficulties in social interactions. Academic impacts include a decrease in motivation and learning performance. To address this issue, the study suggests a holistic approach in the Islamic education curriculum that encompasses character and moral formation, as well as the implementation of strict policies and awareness training for staff and administrators of boarding schools. The ultimate goal is to shape students with strong morality and the ability to make positive contributions to society.